2011
DOI: 10.1080/17405629.2011.576858
|View full text |Cite
|
Sign up to set email alerts
|

Identity formation in Italian emerging adults: A cluster-analytic approach and associations with psychosocial functioning

Abstract: The present study examined identity formation in Italian emerging adults using an integrative identity model including commitment making, identification with commitment, exploration in depth, exploration in breadth, and ruminative exploration. Participants were 1,130 university students, aged 18-30 years. In line with previous research, results indicated that, by means of cluster analysis, six identity statuses could be derived: achievement, foreclosure, moratorium, diffused diffusion, carefree diffusion, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
74
2
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 23 publications
4
74
2
4
Order By: Relevance
“…The reason for such a rather avoidant attitude towards identity issues in men is not entirely clear but a possible explanation may lay in sex-role socialization processes and parenting behaviors (with more freedom and less supervision being granted for boys than for girls; Berzonsky, 2008; Berzonsky & Kinney, 2008). Other studies have found women to score higher on exploration in depth and ruminative exploration (Crocetti et al, 2011; Luyckx, Gandhi, Bijttebier, & Claes, 2015; Luyckx, Schwartz, Berzonsky, et al, 2008). These findings could be explained by the fact that women tend to be more indecisive in nature and are more information-oriented when being faced with a challenge (Rassin & Muris, 2005).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The reason for such a rather avoidant attitude towards identity issues in men is not entirely clear but a possible explanation may lay in sex-role socialization processes and parenting behaviors (with more freedom and less supervision being granted for boys than for girls; Berzonsky, 2008; Berzonsky & Kinney, 2008). Other studies have found women to score higher on exploration in depth and ruminative exploration (Crocetti et al, 2011; Luyckx, Gandhi, Bijttebier, & Claes, 2015; Luyckx, Schwartz, Berzonsky, et al, 2008). These findings could be explained by the fact that women tend to be more indecisive in nature and are more information-oriented when being faced with a challenge (Rassin & Muris, 2005).…”
Section: Introductionmentioning
confidence: 82%
“…Individuals in foreclosure and achievement seem to show the most adaptive general functioning, as they score high on self-esteem and well-being (Crocetti, Luyckx, Scrignaro, & Sica, 2011; Schwartz et al, 2011). Conversely, individuals in moratorium and diffusion seem to experience more depressive symptoms, anxiety, and aggressive behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, our results are in line with earlier research regarding identity formation and the studied outcome variables. The diffusion status has consistently been associated with poor well‐being, psychosocial functioning and need satisfaction in community samples (Crocetti, Luyckx, Scrignaro, & Sica, ; Gandhi et al, ; Lillevoll et al, ; Luyckx et al, ; Waterman, ). Correspondingly, studying a clinical sample of ED patients, we found the most comorbid difficulties in the identity disorder status—a more pathological form of the diffusion status.…”
Section: Discussionmentioning
confidence: 99%
“…Through the use of cluster analysis on this expanded set of identity dimensions, identity clusters similar to Marcia's original four identity statuses (i.e. achievement, foreclosure, moratorium, and diffusion), along with some new statuses, have emerged in North American, Belgian, and Italian samples (Crocetti, Luyckx, Scrignaro, & Sica, 2011;Luyckx, Schwartz, Goossens, Beyers, & Missotten, 2011;Schwartz et al, 2011). These cluster-analytic studies have made it possible to address some of the concerns that have been raised regarding the identity status paradigm.…”
mentioning
confidence: 99%